Szenci Molnár Albert közhelygyűjteménye és Pápai Páriz Ferenc - Förköli, Gábor (Studia Litteraria, 2026)
This essay discusses the handwritten commonplace book of the Hungarian Calvinist intellectual Albert Szenci Molnar (1574–1634), who modelled his notebook on the method of Johann Benz, professor in Strassburg. Adapting his teacher’s system of subject headings, Szenci Molnar focused his attention more and more on matters that he personally considered to be important, such as Hungarian humanism and Calvinist communion theology. The main part of the essay shows how the commonplace-collection was used and augmented by its second owner and scribe, Ferenc Papai Pariz (1649–1716), son of the court preacher of the Prince of Transylvania. Papai, who, after graduating in medicine at Basel, served as Professor of Ancient Greek in Nagyenyed (Aiud, Romania), and became famous for publishing an updated version of Szenci Molnar’s Latin-Hungarian dictionary. He carried the notebook with him during his Western European study trips. Although the materials gathered by him under the commonplace headings point towards less autonomous choices and interests, the entries can be linked to relevant fields, including phraseology, lexicography, bibliography and historia litteraria, medicine, medical botany, and chemical recipes. The material analysis of the document suggests that Papai Pariz not only bound additional leaves to the manuscript, but he also reconstructed its damaged first section. Through his work, Papai Pariz preserved and partially (re)created, one of the most important ego-documents of early Hungarian literature.